Risk Analysis and Mitigation Strategies for the Supply Chain of Bread Products at MSME Muthia Bakery - Witriyan, Fahreza Dwi; Emelda, Muriani; Safar, La Ode Ahmad (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
Muthia Bakery is a micro-scale business producing preservative-free bread and cakes in PPU Regency. This study aims to minimize supply chain risks by identifying, assessing, and developing mitigation strategies tailored to Muthia Bakery’s operations. Using the Supply Chain Operation Reference (SCOR) model, the study mapped key activities (plan, source, make, deliver, and return) to provide a clear structure for risk identification. This mapping facilitated a focused risk analysis using the Failure Mode Effect Analysis (FMEA) method, with Action Priority (AP) used to prioritize critical risks requiring immediate mitigation. Root causes were examined using a Fishbone Diagram, and AHP was applied to prioritize effective mitigation strategies. Results highlight five primary risks, including (1) inaccurate material purchase quantities (RPN 144), mitigated by improving data collection and analysis (weight 0.1000); (2) raw material returns (RPN 144), addressed through SOP development for quality control (weight 0.673); (3) material ordering delays (RPN 140), mitigated via inventory control (weight 0.635); (4) incorrect raw material quantities received (RPN 120), with double verification during ordering (weight 0.444); and (5) production scheduling errors (RPN 105), mitigated by improved time management (weight 0.701). This research provides a systematic risk management approach for micro-scale bakery supply chains, supporting continuity and efficient operational processes.